The lover - Duras, Marguerite (Harper Perennial, 2006)
A sensational international bestseller, and winner of Frances' coveted Prix Goncourt, `The Lover' is an unforgettable portrayal of the incandescent relationship between two lovers, and of the hate that slowly tears the girl's family apart.